Pengaruh Akupresure SP 6 Terhadap Tingkat Dismenore Pada Remaja Putri SMK Pasundan Jatinangor - Ecih Winengsih; Meda Yuliani (2024)
Dysmenorrhea is a condition of pain during menstruation. The incidence of dysmenorrhea worldwide reaches 90% with 10-15% of women experiencing severe dysmenorrhea. Meanwhile in Indonesia it is around 60-70%. If left untreated, it will cause pathological conditions that can affect fertility. One of the effective non-pharmacological treatments is SP 6 acupressure. The aim of the research is to determine the effect of SP 6 acupressure on the level of dysmenorrhea in adolescent girls. The research method uses a quasi-experimental design with a two group pretest-posttest design. The population used was all postpartum mothers, totaling 30 respondents. The sampling technique uses purposive sampling using the Mann Whitney test. The measuring tool uses a questionnaire. Based on statistical tests, results were obtained from the post-test data for the control group and intervention group with a p-value = 0.000, which means <0.05. This means that there is an influence of SP 6 acupressure on the level of dysmenorrhea pain in young women at Pasundan Jatinangor Vocational School. An effort to solve this problem is by holding training related to acupressure.